Integrated Plant Nutrient Management for sustainable agriculture - Singh, S. P.; Singh, Durgesh K.; Singh, R. K.; Singh, D. K. (Indian Farming, 2016)
Integrating the major sources of nutrients that tend to increase the soil fertility and buffering capacity of soil by increasing the water holding capacity, reduction in soil erosion and improvement in C: N ratio in field which are the primary components of IPNM. An increase in the availability of both macro and micro nutrients and increase in the population of beneficial microorganisms in the soil is also observed which ultimately increases the productivity and nutritional quality of produce.